[PP.15.03] LCZ696 COMPARED WITH ANGIOTENSIN II RECEPTOR BLOCKERS FOR PATIENTS WITH HYPERTENSION: A META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS. (September 2016) - Zhao, Y.; Zhao, X.; Li, Ny.; Yu, J.
Abstract : Objective: LCZ696 an angiotensin receptor neprilysin inhibitor has great advantages in the treatment of heart failure. This meta-analysis aim to evaluate the effects of LCZ696 on systolic blood pressure (SBP), diastolic blood pressure (DBP), 24h-ABPM, BP control rate and adverse events versus angiotensin II receptor blockers or other anti-hypertension medicines in patients with primary hypertension. Design and method: We searched the Cochrane Central Register of Controlled Trails (CENTRAL), EMBASE, MEDLINE and PubMed for randomized controlled trials between January 1990 and December 2015. Fourteen studies with 7153 patients (3675 patients in the LCZ696 group and 2507 patients in the ARB or other combined medication were included. The blood pressure and adverse effects in patients with hypertension (systolic/diastolic blood pressure>=140/90 mmHg) were used as evaluation indicators. Results: The results showed that LCZ696 was more effective in lowing SBP(SMD = −8.06 mmHg; 95% CI, −14.91–1.21; P < 0.01), DBP (SMD = −6.52 mmHg; 95% CI, −7.95–5.10; P < 0.01), 24-h-ABPM (SMD = −9.18 mmHg; 95% CI, −10.23–8.12, P < 0.01) than Placebo. The LCZ696 has a higher BP control rate compared to control group (OR = 3.56; 95% CI, 2.89–4.37; P < 0.01), but there was no statistical differences in the rates of serious adverse events between LCZ696 and control group. LCZ696 was more effective in reducing SBP (SMD = −4.652 mmHg; 95% CI, −10.72–1.42; P < 0.01), DBP (SMD = −2.012 mmHg; 95% CI, −2.46–1.56; P < 0.01), 24h-ABMP (SMA = −3.052 mmHg; 95% CI, −4.37–1.72; P < 0.01) compared with ARBs. LCZ696 has a better effect on blood pressure control compared to ARB (OR = 1.50; 95% CI, 1.32–1.71; P < 0.01). There was no significant difference with adverse events incidence between LCZ696 and ARB (OR = 0.92; 95% CI, 0.77–1.10; P < 0.01). For the different dose of LCZ696, the SBP (SMD = 2.70 mmHg; 95% CI, 1.55–3.86; P < 0.01), DBP (SMD = 0.64 mmHg; 95% CI, 0.12–1.15; P < 0.01) and 24h-ABMP (SMD = 3 mmHg; 95% CI, 1.61–4.39; P < 0.01) reduction were lower in the high dose group compared to the low dose group. High-dose LCZ696 has a better blood pressure control rate (OR = 0.85; 95% CI, 0.75–0.96; P < 0.01). The incidence of adverse events was similar in these two difference dose arms (OR = 1.24; 95% CI, 0.64–2.41; P < 0.01) Conclusions: This meta-analysis suggested that the anti-hypertensive effect of LCZ696 might be superior to an angiotensin II receptor blocker. However, further prospective studies assessing the efficacy and safety of LCZ696 are needed.